2021
DOI: 10.1177/17588359211006680
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T-lymphocyte infiltration and chemokine predict long-term patient survival independently of tumor mutational burden in triple-negative breast cancer

Abstract: Background: Cytotoxic T-lymphocyte (CTL) infiltration into tumor is a positive prognostic factor in breast cancer. High tumor mutational burden (TMB) is also considered as a predictor of tumor immunogenicity and response to immunotherapy. However, it is unclear whether the infiltration of functional CTL simply reflects the TMB or represents an independent prognostic value. Methods: Utilizing The Cancer Genome Atlas (TCGA) breast cancer cohort, we established the Functional Hotness Score (FHS). The associations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
2
8
0
Order By: Relevance
“…Moreover, the significantly higher expression of CD8A and PD-1 in the inflammatory DAMPs subtype may be related to its better DFS and DMFS. These observations are in line with previous reports that TNBC patients with elevated CD8A ( 46 ) and PD-1 ( 47 ) expression can potentially benefit from ICIs. Additionally, these results were successfully validated with the TCGA public database.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the significantly higher expression of CD8A and PD-1 in the inflammatory DAMPs subtype may be related to its better DFS and DMFS. These observations are in line with previous reports that TNBC patients with elevated CD8A ( 46 ) and PD-1 ( 47 ) expression can potentially benefit from ICIs. Additionally, these results were successfully validated with the TCGA public database.…”
Section: Discussionsupporting
confidence: 92%
“…CD8A and EIF2AK3 are essential ICD genes in prognostic models. It has been reported that in triple-negative breast cancer (TNBC) patients, the inflammatory DAMP subtype has the most significant proportion of CD8 T cells and is associated with the best predictive outcome, that M2-like macrophages in the suppressor subtype of DAMPs significantly increase inflammation, and that triple-negative breast cancers with high CD8A expression benefit from ICI ( 33 , 34 ). Xu et al.…”
Section: Discussionmentioning
confidence: 99%
“…Hazard ratios for overall survival were calculated using individual log-transformed gene expression. A ‘functional hotness score’ for combined expression of CD8A, DNAM-1, and NKG2D was calculated as previously described [ 51 ].…”
Section: Methodsmentioning
confidence: 99%